2020
DOI: 10.1007/s12253-020-00814-2
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and HER2 Expression in Gastroesophageal Cancer: a Matched Case Control Study

Abstract: Immunotherapy with checkpoint inhibitors serves as a promising treatment strategy in patients with upper gastrointestinal (GI) tumors. Human epidermal growth factor receptor 2 (HER2) is the only identified therapeutic target in upper GI tumors, whose potential interaction with programmed death-ligand 1 (PD-L1) is unknown. The aim of this study was the investigation of PD-L1 and HER2 in upper GI tumors. We retrospectively identified patients with HER2 positive gastroesophageal cancers and matched them with a HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Using patient gastric cancer tissue for DSP analysis and organoid cultures derived from HER2-positive and -negative gastric cancer patients, our present study documents that HER2 and PD-L1 were jointly detected in gastric cancer. Our data is strongly supported by published studies that have performed extensive immunohistochemical and fluorescence in situ hybridization to show that HER2 and PD-L1 are not only co-expressed but related to the gastric cancer stage and lymph node metastasis [ 36 , 37 , 38 , 39 , 40 , 41 ]. We used autologous gastric cancer patient-derived organoid/immune cell co-culture models [ 30 ] to identify the mechanisms by which HER2 regulates the expression of PD-L1 in gastric cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Using patient gastric cancer tissue for DSP analysis and organoid cultures derived from HER2-positive and -negative gastric cancer patients, our present study documents that HER2 and PD-L1 were jointly detected in gastric cancer. Our data is strongly supported by published studies that have performed extensive immunohistochemical and fluorescence in situ hybridization to show that HER2 and PD-L1 are not only co-expressed but related to the gastric cancer stage and lymph node metastasis [ 36 , 37 , 38 , 39 , 40 , 41 ]. We used autologous gastric cancer patient-derived organoid/immune cell co-culture models [ 30 ] to identify the mechanisms by which HER2 regulates the expression of PD-L1 in gastric cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Although some studies focused on the expression of PD-L1 and HER-2 in gastric cancer, the results of these studies are not consistent. Some researchers have found that expression of PD-L1, a potential biomarker for the immunotherapy response, was observed in HER-2 positive and negative patients to a similar extent, and its presence was not influenced by the HER-2 status ( 28 ). However, it has also been studied that the PD-L1 expression in GC is significantly correlated with HER2-negative status ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“… 3 A comprehensive study by “The Cancer Genome Atlas” (TCGA) consortium reported 4 molecular subtypes of GC: chromosomal instability (CIN), microsatellite instability-high (MSI), genomically stable, and Epstein-Barr virus (EBV) molecular subtypes. 5 However, the clinical significance of these subtypes has not been clearly clarified. The Asian Cancer Research Group (ACRG) reported 4 molecular subtypes of GC including microsatellite-stable (MSS)/TP53-, MSS/TP53+, MSI, and epithelial-to-mesenchymal transition (EMT) subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the subclassification by molecular testing might increase the complexity of classification, identifying subtypes of gastric cancer based on molecular and genetic features is necessary to select targeted treatment to increase survival rate in the patients with gastric cancer. 5 Based on previous studies, multiple molecular classification has been introduced. However, there is a need for comprehensive molecular classification that correlates with histological features, clinical outcome, and prognosis of the gastric cancer.…”
Section: Introductionmentioning
confidence: 99%